Theatrical aesthetic and receiving text Reading in the play (Ahel Alcahve) Tawfiq al-Hakim (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Coupled drama recipient since ancient times, and constitute the pleasure derived by the theatrical text by the act of reading and viewing impetus to the demand of the receiver on the play that show, and the direct contact between supply playwright and the recipient is an advantage unique to the theatrical art from other other arts; it is not separated from the receiver any technical barriers, and is a recipient corner base in theatrical production. Tawfiq al-Hakim has been realized that the process of theatrical communication has to be the presence of five main channels cannot be dispensed with, a playwright, director, actor, and stenographer, and the receiver; therefore Tawfiq al-Hakim work to embody these channels in the theater in general, and play (AhelAlcahve) in particular.